An efficient algorithm for prioritizing NEA physical observations. (30th January 2017) - Cortese, M.; Perozzi, E.; Micheli, M.; Borgia, B.; Dotto, E.; Mazzotta Epifani, E.; Ieva, S.; Barucci, M. A.; Perna, D.
Abstract: The present near‐Earth asteroids (NEA) discovery rate has surpassed 1500 objects per year, thus calling for extensive observation campaigns devoted to physical characterization in order to define successful mitigation strategies in case of possible impactors. A tool is presented which, through a prioritization algorithm, aims to optimize the planning and the execution of NEA physical observations. Two ranking criteria are introduced, Importance and Urgency, accounting for the need of satisfying the two basic observational modes for physical characterization, that is, rapid response and large observing programs, aimed at selecting targets for exploration and mitigation space missions. The resulting tool generates a daily table of observable targets and it can also be run as a stand‐alone tool in order to provide future observing opportunities at a specific date of interest. It has been developed and implemented within the framework of the NEOShield‐2 EU/HORIZON 2020 Project; the output of the prioritization algorithm is publicly available, in tabular format, on the NEOShield‐2 NEO Properties Portal (http://www.neoshield.net/the-neoshield-project/project-activities/neo-properties-portal ), reachable from the main page of the Project website (http://www.neoshield.eu ).